Designing an Enterprise Architecture for Holistic Governance in Private Higher Education Institutions: A Strategic Approach for Enhanced Quality and Value Creation - Desfiandi, Andi; Singagerda, Faurani Santi; Sari, Novita; Herwanto, Riko Herwanto (Universitas Dharma Wacana, 2024)
Private Higher Education Institutions (PHEIs) play a significant role in advancing educational opportunities and national competitiveness, yet they face critical challenges in governance, resource efficiency, and stakeholder satisfaction. This study proposes a comprehensive governance framework integrating Total Quality Management (TQM), Enterprise Architecture (EA), and value creation strategies to address these challenges. Using Structural Equation Modeling (SEM) and qualitative insights from pilot implementations at Indonesian PHEIs, the framework identifies key interdependencies among service quality, institutional strategies, and operational outcomes. The results demonstrate that aligning academic and non-academic systems with strategic objectives enhances governance effectiveness, stakeholder engagement, and institutional performance. This research provides practical recommendations for policymakers and practitioners, highlighting the importance of technology adoption, continuous feedback, and capacity building for sustainable governance transformation